Minimizing human infection from Escherichia coli O157:H7 using GUMBOS - Cole, Marsha R. (Oxford University Press, 2013)
OBJECTIVES: Reduction in faecal shedding of Shiga toxin-producing enterohaemorrhagic Escherichia coli (EHEC) in food-producing animals is a viable strategy to minimize human disease initiated by exposure to these microorganisms. To this end, an intervention strategy involving the electrostatic hybridization of two commonly used anti-infective agents for veterinary practice (i.e. chlorhexidine and ampicillin) was evaluated to curtail EHEC-transmitted disease from ruminant sources. Chlorhexidine di-ampicillin is a novel group of uniform material based on organic salts (GUMBOS) with inherent in vitro antibacterial activity that comes from its parent antimicrobial ions, chlorhexidine and ampicillin. METHODS: Antibacterial activities for chlorhexidine diacetate, sodium ampicillin, chlorhexidine di-ampicillin and stoichiometrically equivalent 1 : 2 chlorhexidine diacetate : sodium ampicillin were assessed using the serial 2-fold dilution method and time–kill studies against seven isolates of E. coli O157:H7 and one non-pathogenic E. coli 25922. Further studies to investigate synergistic interactions of reacted and stoichiometrically equivalent unreacted antimicrobial agents at MICs and possible mechanisms were also investigated. RESULTS: Synergism and in vitro antibacterial activities against EHEC were observed in this study, which suggests chlorhexidine di-ampicillin could be a useful reagent in reducing EHEC transmission and minimizing EHEC-associated infections. Likewise, chlorhexidine di-ampicillin reduced HeLa cell toxicity as compared with chlorhexidine diacetate or the stoichiometric combination of antimicrobial agents. Further results suggest that the mechanisms of action of chlorhexidine di-ampicillin and chlorhexidine diacetate against E. coli O157:H7 are similar. CONCLUSIONS: Reacting antimicrobial GUMBOS as indicated in this study may enhance the approach to current combination drug therapeutic strategies for EHEC disease control and prevention.